Chemical characterization and biotechnology applications of fungal glucans. - Silva, MDC da; Martinez, P. F.; Izeli, N. L.; Silva, I. R.; Vasconcelos, AFD; Cardoso, M. D.; Stelutti, R. M.; Giese, E. C.; Barbosa, A. D. (Soc Brasileira Quimica, 2006)
This article gives an overview of exopolysaccharides produced by fungi. The structural characterization of beta-D-(1 -> 3) and beta-D-(1 -> 3, 1 -> 6)-glucans is discussed focusing on different chemical and physical procedures. The industrial applications are also considered mainly from the point of view of human health.
Keywords: exopolysaccharides; glucans; structural characterization